PENGARUH KOMPOS KULIT KAKAO DAN NPKTERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) - Fenti Wahyuni; Husna Yetti; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The needs for ground nut in Riau is always increasing but peanutproduction in Riau is still low. The efforts in increasing the yields of ground nut plants can be done by giving fertilizer optimally. The using of cocoa peel compost and NPK-fertilizer is one of the way that can be done in increasing the yields of ground nut plants. This research aims to find out the effect of cocoa peel compost and NPK-fertilizer interaction on the growth and yield of ground nut plants (Arachis hypogaea L.) and the optimal dosage.This research was carried out at the Experimental Garden of the Faculty of Agriculture,Riau University. The research was conducted for 3 months from May to August 2018. The research was conducted experimentally in factorial 4x4 by using a completely randomized design (CRD). The first factor was cocoa peel compost levels (0, 0.5, 1 dan 1.5kg.plot-1). The second factor was the dosage of NPK-fertilizer (0, 1, 2 dan 3 g.plot-1.). The parameters observed were plant height, stem diameter, plant growth rate (LPT), age of flowering, the percentage of effective root nodules, number of pods per sample, the percentage of peas pithy, 100 seeds weight and seeds weight per m2. The data obtained were analyzed of variance if significantly in different, then would be continued with DNMRT test at the level of 5%. The result of the research showed that cocoa peel compost increased plant height, stem diameter, plant growth rate, age of flowering, number of pods per sample and weight of 100 seeds. The treatment of cocoa peel compost1.5 kg.plot-1 was the best dosage of all the treatments. The treament of NPK-fertilizer 1 g.plot-1 increased the percentage of effective root nodules 81.20%. The treament of NPK-fertilizer 3 g.plot-1 increased the percentage of pithy pods and seeds weight per m2. The interaction of cocoa peel compost 1.5 kg.plot-1 and 3 g.plot-1 of NPK-fertilizer produced the highest percentage of pithy pods 92,08%. Peanut production the treatment of cacao peel compost 1.5 kg.plot-1and 3 g.plot-1 NPK-fertilizer 183,75 g (1,84 tons.ha-1) Key words:ground nut plant, cocoa peel compost, NPK fertilizer